The implementation of the sale and purchase agreement in the all-you-can-eat system: A study of consumer protection law no. 8 of 1999 and the perspective of the shafi'i school - Siska Handayani; Muhammad Nur Iqbal (Journal of Law Science, 2026)
The All You Can Eat (AYCE) dining system, which allows consumers to consume unlimited food for a fixed price, has become increasingly popular in modern culinary businesses. However, this system has generated debate from the perspective of Islamic economic law, particularly concerning issues of contractual clarity (ta?y?n), uncertainty (gharar), and fairness between sellers and consumers. This study examines the AYCE system from two legal perspectives: Indonesian Consumer Protection Law, specifically Law No. 8 of 1999, and the Islamic jurisprudential perspective of the Sh?fi?? school. The objective of this research is to analyze the conformity of AYCE practices with consumer protection principles and the requirements of a valid sale contract according to the Sh?fi?? madhhab. This study employs a normative-empirical research method with a conceptual approach, analyzing legal texts, fiqh doctrines, and empirical practices in AYCE businesses. The findings indicate that, from the perspective of positive law, the AYCE system is legally permissible provided that consumers receive clear, accurate, and non-misleading information, and that no element of coercion is present. From the Sh?fi?? perspective, the validity of the transaction depends on mutual consent (tar???) and transparency between the seller and buyer. Although the AYCE system contains elements of ambiguity in terms of portion size, consumption time limits, and the imposition of fines, such ambiguities are tolerated as long as they do not result in harm (?arar) or injustice to either party. This study contributes to contemporary Islamic economic discourse by providing a legal and jurisprudential framework for understanding modern consumption systems and serves as a reference for Muslim business practitioners and academics in aligning commercial practices with both consumer protection law and Sharia principles.